Chirality Construction from Preferred π-π Stacks of Achiral Azobenzene Units in Polymer: Chiral Induction, Transfer and Memory - Miao, Tengfei (Polymers (Basel), 2018)
The induction of supramolecular chirality from achiral polymers has been widely investigated in composite systems consisting of a chiral guest, achiral host, and solvents. To further study and understand the process of chirality transfer from a chiral solvent or chiral molecules to an achiral polymer backbone or side-chain units, an alternative is to reduce the components in the supramolecular assembled systems. Herein, achiral side-chain azobenzene (Azo)-containing polymers, poly(6-[4-(4-methoxyphenylazo) phenoxy] hexyl methacrylate) (PAzoMA), with different M(n)s, were synthesized by atom transfer radical polymerization (ATRP). Preferred chirality from supramolecular assembled trans-Azo units of PAzoMAs is successfully induced solely by the neat limonene. These aggregates of the polymers in limonene solution were characterized by circular dichroism (CD), UV-vis spectra, and dynamic light scattering (DLS) under different temperatures. The temperature plays an important role in the course of chiral induction. Meanwhile, supramolecular chirality can be constructed in the solid films of the achiral side-chain Azo-containing polymers that were triggered by limonene vapors. Also, it can be erased after heated above the glass transition temperature (T(g)) of the polymer, and recovered after cooling down in the limonene vapors. A chiroptical switch can be built by alternately changing the temperature. The solid films show good chiral memory behaviors. The current results will facilitate studying the mechanism of chirality transfer induced by chiral solvent and improve potential application possibilities in chiral film materials.